2021
DOI: 10.1097/cce.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hyperoxia, Supplemental Oxygen, and Mortality in Critically Injured Patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…In the interim, supplemental oxygen therapy via mask-reservoir device with flow rate of 15L/min for polytrauma patients undoubtedly prevents the mortality and morbidity associated with hypoxia. 45 Target oxygen therapy should be considered after initial stabilization in trauma patients. Hypocalcemia: This can occur in patients with polytrauma due to rhabdomyolysis and massive blood transfusion.…”
Section: Managing Associated Risks During Polytrauma Managementmentioning
confidence: 99%
“…In the interim, supplemental oxygen therapy via mask-reservoir device with flow rate of 15L/min for polytrauma patients undoubtedly prevents the mortality and morbidity associated with hypoxia. 45 Target oxygen therapy should be considered after initial stabilization in trauma patients. Hypocalcemia: This can occur in patients with polytrauma due to rhabdomyolysis and massive blood transfusion.…”
Section: Managing Associated Risks During Polytrauma Managementmentioning
confidence: 99%
“…2 Commonly defined as a partial pressure of oxygen (PaO2) >100mmHg or oxygen saturation (SpO2) >96%, the use of hyperoxia remains controversial. [3][4][5][6] Potential benefits of hyperoxia include ischemic-preconditioning 7 and enhanced neutrophil oxidative killing function. 8 However, hyperoxia may also lead to harmful consequences following cardiac surgery, including initiating an inflammatory cytokine cascade, 9 reactive oxygen species (ROS) formation, 10 ischemiareperfusion injury, 11 and decreased postoperative PaO2: FiO2 ratio.…”
Section: Oxygenation Targets In Cardiac Surgery: Finding the Sweet Spotmentioning
confidence: 99%
“…7,8,10,11 Our group has demonstrated that hyperoxia is both common and associated with a greater risk for mortality in critically ill trauma patients. 12 The effects of hyperoxia in TBI patients, however, remain controversial. Recent studies have yielded conflicting conclusions.…”
Section: Introductionmentioning
confidence: 99%